Effect of polarity‐reversal and electrical intensity on the oil removal from soil. Issue 3 (13th February 2014) - Li, Tingting; Guo, Shuhai; Wu, Bo; Zhang, Lingyan; Gao, Yongchao
Abstract BACKGROUND Although electro‐bioremediation (EK‐Bio) is effective at removing organic contaminants from soil, the role of electrical intensity (EI) and polarity‐reversal (PR) remains unclear. Two electrokinetic reactors (ER I and II) with six treatments (EK‐I, EK‐PR‐I, Bio‐I, EK‐Bio‐I, EK‐Bio‐PR‐I and EK‐PR‐II) were applied for 42 days to examine the effect of EI and PR on oil EK‐Bio remediation. RESULTS The final oil degradation rate in EK‐Bio‐PR‐I was 27.8%, representing an increase of 18.4%, 11.3% and 7.6% compared with EK‐I, Bio‐I and EK‐Bio‐I, respectively. Soil pH remained at around 6.6, and the average bacterial counts increased from 7.66 to 8.41 log10 cfu g‐1 dry soil by the end of EK‐Bio‐PR‐I. There was a significant positive linear correlation between EI and the oil degradation rate in EK‐I (y = 0.6919x + 9.2278; Pearson correlation coefficient = 0.9887). The simulated oil degradation rate was assessed according to the above equation in an amplification experiment (EK‐PR‐II), and the observed oil degradation rate showed no significant difference with the simulated data (P > 0.05). CONCLUSION EI and PR have positive effects on oil degradation efficiency and soil bacteria, indicating that EK‐Bio with appropriate EI and periodic PR is the best approach for removing oil from soil. © 2014 Society of Chemical Industry